2017
DOI: 10.2134/jeq2016.09.0344
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Phosphoric Acid in Biochar Formation: Synchronously Improving Carbon Retention and Sorption Capacity

Abstract: Pretreatment of biomass with phosphoric acid (HPO) for biochar production was expected to improve carbon (C) retention, porosity structure, and the sorption ability of biochar. This study investigated the interaction of phosphorus with the C structure to elucidate the mechanisms by which HPO simultaneously captured C and created micropores. Sawdust was soaked in diluted HPO and dried for pyrolytic biochar generation at 350, 500, and 650°C. Results showed that HPO pretreatment resulted in 70 to 80% of biomass C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(80 citation statements)
references
References 53 publications
(67 reference statements)
1
72
0
Order By: Relevance
“…The commonly used oxidants are HCl, HNO 3 , H 2 O 2 , H 3 PO 4 , etc. [56][57][58][59][60]. Although the specific surface area of biochar modified by HCl, HNO 3 , and H 2 O 2 has little difference, compared with biochar modified by HCl, the biochar modified by HNO 3 contains more acidic oxygen-containing functional groups [61] and has stronger adsorption capacity for NH 3 -N. Compared with other acids, biochar modified by H 3 PO 4 has more advantages in removing Pb pollution.…”
Section: Chemical Oxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…The commonly used oxidants are HCl, HNO 3 , H 2 O 2 , H 3 PO 4 , etc. [56][57][58][59][60]. Although the specific surface area of biochar modified by HCl, HNO 3 , and H 2 O 2 has little difference, compared with biochar modified by HCl, the biochar modified by HNO 3 contains more acidic oxygen-containing functional groups [61] and has stronger adsorption capacity for NH 3 -N. Compared with other acids, biochar modified by H 3 PO 4 has more advantages in removing Pb pollution.…”
Section: Chemical Oxidationmentioning
confidence: 99%
“…Although the specific surface area of biochar modified by HCl, HNO 3 , and H 2 O 2 has little difference, compared with biochar modified by HCl, the biochar modified by HNO 3 contains more acidic oxygen-containing functional groups [61] and has stronger adsorption capacity for NH 3 -N. Compared with other acids, biochar modified by H 3 PO 4 has more advantages in removing Pb pollution. The increased specific surface area and pore volume, as well as the role of phosphate precipitation, increase the biochar adsorption capacity of Pb [60].…”
Section: Chemical Oxidationmentioning
confidence: 99%
“…The adsorption capacity was pH dependent, confirming the active adsorption site of oxygen-containing functional groups on biochars surface. The H 3 PO 4 treatment prior to pyrolysis of pine tree sawdust increased the total pore volume and the content of micropores (Chu et al 2018;Zhao et al 2017). The P-O bond formed in the C structure acted like a backbone to prevent micropores clap during the pyrolysis, which enhanced the adsorption capacity for organic pollutants (Chu et al 2018).…”
Section: Chemical Modificationmentioning
confidence: 99%
“…Many researchers only emphasized its capability and efficiency in contaminant removal, but neglected its stability changes (Bogusz et al 2015;Tang et al 2013). Due to the changed physicochemical properties of EngBCs, their stability definitely has been changed because most of the modification method involved harsh treatments (such as high temperature and low pH) (Iriarte-Velasco et al 2016;Rajapaksha et al 2016;Zhao et al 2017). These property changes of biochars also can alter their interactions with contaminants (e.g., heavy metal and organic pollutants), as well as mineral and organic components of soil/sediments.…”
Section: Introductionmentioning
confidence: 99%
“…So, drying pristine cauliflower leaves to remove moisture was of great necessity. Other common biochar materials contain similar elemental contents as the CLB, which indicated that a biochar sorbent was successfully prepared at 120 • C carbonization temperature under the air atmosphere [12,25]. CLB contained higher elemental carbon than CL, while the oxygen and hydrogen content of CLB was lower than that of CL, leading to the lower ratio of H/C and O/C of CLB.…”
Section: Statistical Analysesmentioning
confidence: 95%